An experimental evaluation of competitive and thermal effects on brown trout (Salmo trutta) and Bonneville cutthroat trout (Oncorhynchus clarkii utah) performance along an altitudinal gradient - McHugh, Peter; Budy, Phaedra (Canadian journal of fisheries and aquatic sciences, 2005)
Temperature-mediated competition (i.e., dominance shifts between species depending on temperature) may explain the segregation of salmonid species along altitudinal stream gradients. We evaluated this hypothesis for exotic brown trout (Salmo trutta) and native Bonneville cutthroat trout (Oncorhynchus clarkii utah) by rearing them in experimental sympatry and allopatry using enclosures constructed at six sites spaced along a 45-km segment of a mountain stream. For both species, we compared condition and growth between allopatric and sympatric treatment groups. We found that brown trout negatively affected cutthroat trout performance, whereas cutthroat trout failed to impart an effect in the reverse direction, regardless of temperature. Thus, we documented asymmetric competition between these species but found little evidence indicating that its outcome was influenced by temperature. Brown trout cutthroat trout segregation is therefore unlikely to be due to temperature-mediated competition. Instead, brown trout may have displaced cutthroat trout from downstream areas through competition or other mechanisms, while abiotic factors preclude their (brown trout) invasion of upper elevations. Given the magnitude of effect observed in our study, we recommend that brown trout receive greater consideration in cutthroat trout conservation.